Fighting Shirley Chisholm - Haskins, James, 1941- (New York : Dial Press, 1975)
A biography of the first black congresswoman and the first black woman to run for the presidential nomination.
Includes index
Bibliography: p. 201-205
Keywords: Chisholm, Shirley, 1924 -- Juvenile literature